Introduction to this Issue - Margaret Davies; Bronwyn Naylor; Anne Orford; Dianne Otto (Legal Education Review)
The papers collected in this edition of The Legal Education Review were all presented at the second Feminist Legal Academics Workshop which was held at the Australian National University on February 23 and 24, 1995. The conference was attended by approximately 80 feminist academics and public servants from Australia, New Zealand, Canada, and Japan, and represented an extraordinarily successful gathering of feminists involved in the teaching and administration of the law. The large and enthusiastic attendance was clearly a symptom of the growing awareness among legal academics of the importance of gender-sensitive reform of the traditional law curriculum. The prevailing context, however, is also one in which traditional law teaching has been identified by the Federal Government as a major contributor to inequality before the law. Combined with current developments in legal pedagogy — including what has been called a “shifting paradigm” in thinking about the law — the conditions are conducive to major changes in legal education.